The impact of behavior change communication on healthy living movement-related knowledge and behavior among adolescents: A mixed-methods study - Siswati, Tri; Widiyanto, Santo Yoseph Didik; Olfah, Yustiana; Setyowati, Setyowati; Paramashanti, Bunga Astria (YCAB Publisher & IAKMI SULTRA, 2023)
Background: Behavior change communication (BCC) is a validated health communication technique for influencing changes in knowledge and behaviors. Objective: This study aimed to investigate the impact of BCC on the knowledge and practice of the Healthy Living Movement (HLM) or called Gerakan Masyarakat Hidup Sehat (Germas). Methods: This was a mixed-methods study. A single group pre-posttest design was conducted in Yogyakarta and Central Java, Indonesia, from May to October 2019. Participants are all first-year students from selected schools, as many as 713 persons. The intervention was the BCC strategy, while the outcomes were knowledge and behavior. The BCC intervention was carried out through several stages, from need assessment, designing an educational intervention, the intervention with pre-and post-test, evaluation, and networking. Specifically, the educational intervention was conducted 60 minutes weekly for three weeks. The contents of HLM included a balanced diet, physical activity, and the relationship between health and academic achievement. The knowledge and practice scores were measured using a structured questionnaire before and after the BCC intervention. STATA 13 was used to calculate the mean difference (MD) using a t-test. To evaluate the BCC intervention, qualitative in-depth interviews were used, and data were analyzed thematically. Results: BCC intervention significantly increased knowledge and behavior on a balanced diet, physical activity, and the relationship between health and academic achievement (p <0.05). Internal social norms were carried out through the HLM campaign and declarations, as well as assigning HLM ambassadors, while advocacy by establishing networking between universities, schools, and public health centers strengthened the sustainability program. Conclusion: BCC intervention improves knowledge and behavior among adolescents. Moreover, the environment is crucial to support and maintaining the program.